The Relationship Between Anti-Hypertensive Drugs and Cancer: Anxiety to be Resolved in Urgent - Yang, Rong; Zhang, Yonggang; Liao, Xiaoyang; Yao, Yi; Huang, Chuanying; Liu, Lixia (Frontiers in Pharmacology, 2020)
Hypertension is the prevailing independent risk factor for cardiovascular disease worldwide. Anti-hypertensive drugs are the common and effective cure for lowering blood pressure in patients with hypertension. However, some large-scale clinical studies have pointed out that long-term ingestion of some oral anti-hypertensive drugs was associated with risks of incident cancer and the survival time. In contrast, other studies argue that anti-hypertensive drugs are not related to the occurrence of cancer, even as a complementary therapy of tumor treatment. To resolve the dispute, numerous recent mechanistic studies using animal models have tried to find the causal link between cancer and different anti-hypertensive drugs. However, the results were often contradictory. Such uncertainties have taken a toll on hypertensive patients. In this review, we will summarize advances of longitudinal studies in the association between anti-hypertensive drugs and related tumor risks that have helped to move the field forward from associative to causative conclusions, in hope of providing a reference for more rigorous and evidence-based clinical research on the topic to guide the clinical decision making.